Characteristic of Freshness Ulva lactuca Under Different Temperatures at Short-term Storage - Jasmadi Jasmadi; C.D. Poeloengasih; H. Novianty; A.R. Sefrienda; Sandi Permadi; I.T. Suryaningtyas; B. Kumayanjati; D.E.D. Setyono (Journal of Aquaculture and Fish Health, 2023)
Ulva sp. is green macroalgae that very potential for producing food with high nutrients content. This species is found on a coastline in intertidal zone of Indonesia’s waters. There have been several research to this species start from post-harvest handling, nutrition, probiotic, and its ulvaran, however the information of effect of temperature storage to Ulva lactuca freshness is still lack. This study was undergone to evaluate the freshness quality of Ulva lactuca by sensory changes in different temperatures short-term storage. In order to evaluate the effect of the different storage circumstances, the fresh U. lactuca was collected from its natural habitat (intertidal zone of Sepanjang Coast, Yogyakarta Indonesia). It was rinsed from debris and epiphyte, stored in transparent polyethylene bag, and were stored in 4 °C, 15-20 °C and room temperature for five days. Color, pH, ash, moisture, crude protein, chlorophyl, Total Plate Count, sensory analysis was undergone along the storage period. The sensory evaluation score of U. lactuca in 4 °C were more than 6, and better than other storages. The crude protein (U. lactuca stored in 4 °C) decreased significantly on day 4 by 5.53%, it was lower than others. The TPC of all samples varied from 147x103in 0 days of storage to 2,462.5x103 CFU/ml on the last day of storage. In summaries, sensory scores of U. lactuca are more constant and higher in 4 °C than in other storages, despite minor nutrient content deterioration.